2020
DOI: 10.18388/abp.2020_5418
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 90α inhibitor, PU-H71 in combination with DHEA promoting apoptosis in triple-negative breast cancer cell line MDA-MB-231

Abstract: Due to the lack of markers (ER, PR, and HER-2/Neu) for the molecular-targeted therapies triple-negative breast cancer (TNBC) is more challenging than other subtypes of breast cancer. Moreover, the conventional chemotherapeutic agents are still the mainstay of most therapeutic protocols and eventually turn into a refractory drug-resistance , hence, more efficient therapeutic regimens are urgently required. The present study aimed to elucidate the effects of PU-H71 combined with DHEA on triple-negative breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Notably, heat shock protein 90 (Hsp90), found to be highly expressed in BC, plays a vital role in sustaining cancer cell survival, and is involved in several molecular processes contributing to carcinogenesis. Therefore, inhibiting its function represents a promising avenue for therapeutic intervention [ 41 , 42 ]. In a study targeting TNBC xenografts with the Hsp90 inhibitor, PU-H71, tumor growth was suppressed and a significant killing of TNBC cells was induced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, heat shock protein 90 (Hsp90), found to be highly expressed in BC, plays a vital role in sustaining cancer cell survival, and is involved in several molecular processes contributing to carcinogenesis. Therefore, inhibiting its function represents a promising avenue for therapeutic intervention [ 41 , 42 ]. In a study targeting TNBC xenografts with the Hsp90 inhibitor, PU-H71, tumor growth was suppressed and a significant killing of TNBC cells was induced.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Hsp90 inhibition resulted in a downregulation or inactivation of the Ras/Raf/MAPK pathway and G2M phase, degradation of Akt and Bcl-XL, and inhibition of NF-kb, ERK2, Tyk2, and PKC, both in vivo and in vitro, suggesting that the anti-proliferative effect of PU-H71 directly stems from depleting TNBC cells of these malignancy-driving proteins and that Hsp90 represents a pivotal multimodal target for future therapeutic strategies [ 42 ]. In another study, the combination of PU-H71 with DHEA, a glucose-6-phosphate dehydrogenase (G6PD) inhibitor, demonstrated a synergistic anti-tumor effect on TNBC cells by suppressing Nrf2, a key transcription factor regulating antioxidants and metabolic enzymes and leading to apoptosis, suggesting that G6PD inhibitors could be valuable additions to combination therapies targeting cellular oxidative balance [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that PU-H71 triggers apoptosis of triple-negative breast cancer (TNBC) cells and downregulates expression of key factors such as VEGF, EGFR and Akt, thus inhibiting tumor growth. [217][218][219] A phase I clinical trial assessed the safety and feasibility of combining PU-H71 with nab-paclitaxel in patients with metastatic breast cancer, showing promising results (No: NCT03166085). 220 BIIB021 is a synthetic, novel, and orally available HSP90 inhibitor commonly used for the clinical treatment of solid tumors.…”
Section: Purine-based Compoundsmentioning
confidence: 99%
“…Further structural modification results in the development of PU‐H71. Studies have shown that PU‐H71 triggers apoptosis of triple‐negative breast cancer (TNBC) cells and downregulates expression of key factors such as VEGF, EGFR and Akt, thus inhibiting tumor growth 217–219 . A phase I clinical trial assessed the safety and feasibility of combining PU‐H71 with nab‐paclitaxel in patients with metastatic breast cancer, showing promising results (No: NCT03166085) 220 …”
Section: Hsp90 Inhibitors For Cancer Treatmentmentioning
confidence: 99%